Sensitivity of the multiannual thermal dynamics of a deep pre‐alpine lake to climatic change. Issue 5 (25th March 2014) - Valerio, Giulia; Pilotti, Marco; Barontini, Stefano; Leoni, Barbara
Abstract The study of the multiannual thermal dynamics of Lake Iseo, a deep lake in the Italian pre‐alpine area, is presented. Interflow was found to be the dominant river entrance mode, suggesting future susceptibility of the lake thermal structure to the overall effects of climate change expected in the upstream alpine watershed. A lake model employed the results of a long‐term hydrologic model to simulate the effects of a climate change scenario on the lake's thermal evolution for the period 2012–2050. The model predicts an overall average increase in the lake water temperature of 0.012 °C/year and a reinforced Schmidt thermal stability of the water column in the winter up to 800 J/m2. Both these effects may further hinder the deep circulation process, which is vital for the oxygenation of deep water. Copyright © 2014 John Wiley & Sons, Ltd.